A Brief Interpretation of CCAC Guide on Humane Endpoints of Animals: 2022 Edition - LI Xiaying; WEI Yusheng; TIAN Yonglu; PANG Wanyong (Shiyan dongwu yu bijiao yixue, 2022)
The 2022 Canadian Council On Animal Care (CCAC) guidelines: Identification of Scientific Endpoints, Human Intervention Points, and Cumulative Endpoints (CCAC Guide) supplements existing laboratory animal humane endpoint theory according to the latest available literature. This article summarized the main content of the 2022 CCAC Guide, and elaborated and analyzed the determination, implementation and supervision of the scientific endpoints, humane intervention points, and cumulative endpoints of animal experiments, in order to provide useful reference and information.